Investigating the role of the growth hormone-insulin-like growth factor (GH-IGF) axis as a determinant of male bone mineral density (BMD). - Patel, M; Arden, N; Masterson, L; Phillips, D; Swaminathan, R; Syddall, H; Byrne, C; Wood, P; Cooper, C; Holt, R (2005)
INTRODUCTION: The GH-IGF axis has profound effects on bone metabolism and may be important in the etiology of idiopathic osteoporosis. Serum IGF-I is often low in men with osteoporosis, which may be attributable to GH hypo-secretion or hepatic GH insensitivity. We studied the GH-IGF axis in depth to look for evidence to support these hypotheses. MATERIALS AND METHODS: 28 healthy 60- to 70-year-old men with low, intermediate, or normal BMD were studied. GH secretion was measured by overnight urine collection. GH reserve was assessed by exercise and glucagon stimulation tests. Hepatic IGF-I production was investigated using a GH-IGF-I generation test. Data were analyzed using Pearson's correlation coefficient, linear regression, and analysis of variance. RESULTS: Serum IGF-I was reduced in subjects with low BMD (P = 0.009). There was no difference in GH secretion or reserve between the groups. Overall, GH reserve and IGF-I were positively related but this was attenuated in the low BMD group. However, no statistically significant difference in IGF-I generation capacity between BMD groups was found. CONCLUSIONS: Men with reduced BMD have low IGF-I but normal GH secretion and reserve. Our data suggested, but could not confirm, hepatic resistance to GH as a mechanism for this association.